Curcumin enhances the membrane trafficking of the sodium iodide symporter and augments radioiodine uptake in dedifferentiated thyroid cancer cells via suppression of the PI3K-AKT signaling pathway. Issue 18 (29th July 2021) - Zhang, Li; Xu, Shichen; Cheng, Xian; Wu, Jing; Wang, Xiaowen; Wu, Liying; Yu, Huixin; Bao, Jiandong
Abstract : Curcumin restores the expression of thyroid functional genes, resulting in a significant improvement of radioiodine uptake in dedifferentiated thyroid cancer cells in vitro . Abstract : Radioactive iodine (RAI) is commonly used to treat differentiated thyroid cancer (DTC). A major challenge is the dedifferentiation of DTC with the loss of radioiodine uptake. Patients with distant metastases have persistent or recurrent disease and develop resistance to RAI therapy due to tumor dedifferentiation. Hence, tumor redifferentiation to restore sensitivity to RAI therapy is considered a promising strategy to overcome RAI resistance. In the present study, curcumin, a natural polyphenolic compound, was found to re-induce cell differentiation and increase the expression of thyroid-specific transcription factors, TTF-1, TTF-2 and transcriptional factor paired box 8 (PAX8), and iodide-metabolizing proteins, including thyroid stimulating hormone receptor (TSHR), thyroid peroxidase (TPO) and sodium iodide symporter (NIS) in dedifferentiated thyroid cancer cell lines, BCPAP and KTC-1. Importantly, curcumin enhanced NIS glycosylation and its membrane trafficking, resulting in a significant improvement of radioiodine uptake in vitro . Additionally, AKT knockdown phenocopied the restoration of thyroid-specific gene expression; however, ectopic expressed AKT inhibited curcumin-induced up-regulation of NIS protein, demonstrating that curcumin might improve radioiodine sensitivity via the inhibition of the PI3K-AKT-mTOR signaling pathway. Our study demonstrates that curcumin could represent a promising adjunctive therapy for restoring iodide avidity and improve radioiodine therapeutic efficacy in patients with RAI-refractory thyroid carcinoma.